1985
DOI: 10.1080/07391102.1985.10507632
|View full text |Cite
|
Sign up to set email alerts
|

Z Helix-coil Transition of d(C-Br8G-C-G-C-Br8G) Studied by CD,1H-NMR and IR Spectroscopies

Abstract: The conformation of d(C-Br8G-C-G-C-Br8G) in aqueous solution was studied by CD and 1H-NMR spectroscopy and in condensed phase by IR spectroscopy. Whether in 0.1 M or 3 M NaCl solution or in film the only double helical structure adopted by brominated d(C-G)3 oligomer is the Z form. The IR spectrum of the film presents all the characteristic absorptions of the Z conformation and in particular is indicative of a syn conformation for the central guanosine as well as for the brominated one. Imino proton resonances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…As the temperature is raised, the conformation in this region of the molecule is altered to one in which such accessibility to exchange is diminished. This conformational change may be due to changes in the flexibility of the DNA backbone as the temperature is raised, as has been observed with other oligomers in the Z conformation (Hart-mann et al, 1983;Genest et al, 1987;Taboury et al, 1985). The changes with temperature observed in the 31P NMR spectra are consistent with this notion.…”
Section: Discussionsupporting
confidence: 80%
“…As the temperature is raised, the conformation in this region of the molecule is altered to one in which such accessibility to exchange is diminished. This conformational change may be due to changes in the flexibility of the DNA backbone as the temperature is raised, as has been observed with other oligomers in the Z conformation (Hart-mann et al, 1983;Genest et al, 1987;Taboury et al, 1985). The changes with temperature observed in the 31P NMR spectra are consistent with this notion.…”
Section: Discussionsupporting
confidence: 80%
“…Past work with poly(dG-dC) (6,11,12) and analogs (13,14) has shown that infrared spectroscopy is a sensitive method for detecting the B and Z structures. The same structural forms have been shown to exist in hydrated films and in solutions (13).…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic parameters were deter- [13]. Similarly to the 8-substituted purine oligoribonucleotides, the bulky 8-methyl groups force the oligonucleotide from the B-to the Z-DNA structure [5] [6]. This conformational change is neither observed in the case of the 7-substituted 7-deazaguanine oligonucleotides nor in the case of oligonucleotides containing 7-deazaguanine.…”
mentioning
confidence: 99%
“…In such a Z-DNA structure, the guanine residues adopt the syn/C(3')-endo conformation. The 8-substituents are located in the periphery of the left-handed helix and exposed to the solvent [5] [6].…”
mentioning
confidence: 99%